Role of ADDUCIN Gly460Trp, ACE I/D and AGT M235T Gene Polymorphisms in Genetic Susceptibility to Dia- betic Nephropathy. Issue 2 (April 2015) - Sancakdar, Enver; Ateş, Kadir; Deveci, Dilara Kaman Köksal; Özkan, Yusuf; İlhan, Necip
No abstract available